HUBUNGAN KUALITAS PELAYANAN KARYAWAN RECEPTION FRONT OFFICE DEPARTMENT DENGAN KEPUASAN TAMU MENGINAP DI HOTEL GRAND ROCKY BUKITTINGGI - Ramadeni, Ramadeni; Yuliana, Yuliana; Abrian, Youmil (Journal of Home Economics and Tourism, 2016)
The purpose of this study are: (1) Describe the service quality of reception employess, (2) Describe the customer satisfaction and (3) Analyze the relationship between reception service quality employee towards customer satisfaction who stay over night at Grand Rocky Bukittinggi Hotel. The research is correlational. Research the population of this study are, all the guest who ever stayed at Grand Rocky Bukittinggi Hotel. A sample of 96 customers are taken incidentally. Data was collected using a questionnaire that had been tested for validity and reliability. Furthermore the data were analyze by descriptive and correlation with the help of computer program SPSS version 16.00. The results showed that: (1) The service quality of the reception employee positioned the good category (81,3%), (2) the guest satisfaction positioned the satisfact category (63,5%), and (3) There is a positive and significant relationship between reception employee service quality and the customer satisfaction with the value of r amounted to 0,397 (0,000sig) and interpreted that these two variables has strong enaugh relationship. Â Key words: service quality and guest satisfaction.